Zastosowanie informatycznego systemu zarządzania w przedsiębiorstwie - Chojnacka, Anna (Application of Management Information Systems, 2005)
The article presents in a synthetic way key issues of application of management information systems in an enterprise. It is divided into two sections. The first one highlights theoretical aspects of management information systems. The second section presents results of a survey on actual utilization of the systems conducted in commercial entities.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1081, s. 340-348